2018
DOI: 10.1007/s10460-018-9896-y
|View full text |Cite
|
Sign up to set email alerts
|

How consumers use mandatory genetic engineering (GE) labels: evidence from Vermont

Abstract: Food labels legislated by the U.S. government have been designed to provide information to consumers. It has been asserted that the simple disclosures "produced using genetic engineering" on newly legislated U.S. food labels will send a signal that influences individual preferences rather than providing information. Vermont is the only US state to have experienced mandatory labeling of foods produced using genetic engineering (GE) via simple disclosures. Using a representative sample of adults who experienced … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 34 publications
1
17
0
Order By: Relevance
“…Additionally, it lends support to the work of Bovay and Alston [ 38 ], who assert that the upcoming mandatory GM labeling law in the U.S. will likely be a costly addition to food products and will receive limited attention/use by consumers. In fact, a recent study examining the impact of mandatory bioengineered (BE) labeling used in Vermont indicates that while the label did serve as a useful information source for some consumers, the majority (~66%) did not notice the BE label, limiting its effectiveness [ 39 ]. Moreover, the diversity of methodologies and populations studied in previous literature further complicates the identification of factors that might be influencing the observed non-concordance between attitudes and behavior [ 14 , 16 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, it lends support to the work of Bovay and Alston [ 38 ], who assert that the upcoming mandatory GM labeling law in the U.S. will likely be a costly addition to food products and will receive limited attention/use by consumers. In fact, a recent study examining the impact of mandatory bioengineered (BE) labeling used in Vermont indicates that while the label did serve as a useful information source for some consumers, the majority (~66%) did not notice the BE label, limiting its effectiveness [ 39 ]. Moreover, the diversity of methodologies and populations studied in previous literature further complicates the identification of factors that might be influencing the observed non-concordance between attitudes and behavior [ 14 , 16 , 24 ].…”
Section: Discussionmentioning
confidence: 99%
“…GM-free) label (Liaukonyte et al , 2013). With regard to interest in such a label, the available evidence indicates that those who are younger, highly educated, male and more risk-averse are less likely to be supportive (DeLong and Grebitus, 2017; Kolodinsky et al , 2018) – echoing determinants of attitudes towards GM food. In contrast, women and those with lower levels of education were more likely to highlight the importance of GM food labels (DeLong and Grebitus, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…In 2016 Vermont required a simple disclosure, "produced or partially produced using genetic engineering" on several categories of foods (Vermont General Assembly, 2014). Respondent samples from Vermont have been used in several studies as the test case for the impacts of mandatory labels on consumer behavior and markets and the Vermont experience has been cited by others investigating the impact of mandatory labeling policies (Bovay & Alston, 2018;Dai et al, 2006;Dunham, 2016;Esposito & Kolodinsky, 2007;Kolodinsky, 2008;Kolodinsky & Lusk, 2018;Kolodinsky et al, 2004Kolodinsky et al, , 2019Wang et al, 1998;Yeh et al, 2019). In addition to products that already meet the NBFDS standard, voluntary labels with a simple disclosure have persisted in the state.…”
Section: Study Objectivesmentioning
confidence: 99%
“…Because there were no positive labels in the marketplace at this time, these were non-GM labels, which were more often looked at by women and people under the age of 65 years, when compared to men and older people. Kolodinsky et al (2019) found that immediately after the implementation of the Vermont mandatory GM labeling law, 34% of respondents reported seeing the "produced or partially produced using genetic engineering label. "…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation